2022
DOI: 10.3390/w14213549
|View full text |Cite
|
Sign up to set email alerts
|

Hybridized Adaptive Neuro-Fuzzy Inference System with Metaheuristic Algorithms for Modeling Monthly Pan Evaporation

Abstract: Precise estimation of pan evaporation is necessary to manage available water resources. In this study, the capability of three hybridized models for modeling monthly pan evaporation (Epan) at three stations in the Dongting lake basin, China, were investigated. Each model consisted of an adaptive neuro-fuzzy inference system (ANFIS) integrated with a metaheuristic optimization algorithm; i.e., particle swarm optimization (PSO), whale optimization algorithm (WOA), and Harris hawks optimization (HHO). The modelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…In line with our results, previous works have also demonstrated that employing an ensemble modeling approach can yield improved model performance compared to using a single model (Adnan Ikram et al., 2022; Adnan et al., 2021; Bien et al., 2023; Moayedi & Dehrashid, 2023; Pham et al., 2020, 2021, 2022). By combining multiple models, researchers can harness the collective knowledge and strengths of each model to make more accurate predictions or decisions.…”
Section: Resultssupporting
confidence: 92%
“…In line with our results, previous works have also demonstrated that employing an ensemble modeling approach can yield improved model performance compared to using a single model (Adnan Ikram et al., 2022; Adnan et al., 2021; Bien et al., 2023; Moayedi & Dehrashid, 2023; Pham et al., 2020, 2021, 2022). By combining multiple models, researchers can harness the collective knowledge and strengths of each model to make more accurate predictions or decisions.…”
Section: Resultssupporting
confidence: 92%
“…Nonetheless, using statistically based methods to solve a highly non-linear issue such as flyrock and rock fragmentation can be a challenging and difficult endeavor. Many attempts are conducted to solve engineering problems by using artificial intelligence and soft computing techniques [16][17][18][19][20][21][22][23][24][25]. Therefore, the application of intelligent machine learning, such as artificial intelligence (AI) and soft computing (SC), could have relevance and benefit when attempting to solve issues related to this type.…”
Section: Introductionmentioning
confidence: 99%